(untitled) - Jagelcak, Juraj (Doprava a spoje, 2010)
This paper describes new packing and load securing procedure for palletized chemicals in paper bags transported in semi-trailers and containers by road, rail and sea transport by one company. The aim of the work was to solve the problems with limited pallet height of the packing line and following problems with safe carriage because of cargo transport unit utilisation. Transported chemicals are hazardous class 9.